AI, PIRACY, AND THE DEATH OF OWNERSHIP - Diyorbek Norqulov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The rise of artificial intelligence is forcing a reckoning with the very foundations of intellectual property law. For centuries, copyright and patent regimes have relied on the premise of scarcity: that works are original, finite, and owned by identifiable creators. Yet AI systems undermine these assumptions by generating infinite outputs at negligible cost, blurring authorship, and accelerating global access to culture. This article situates the debate historically, showing how piracy—from 19th-century American publishers pirating Dickens to cassette tape sharing in the 1980s—has often been a driver of cultural dissemination rather than mere criminality. Today, in places like Uzbekistan, the reliance on “pirated” knowledge is not deviance but necessity, enabling students, entrepreneurs, and creators to participate in global knowledge economies. By analyzing contemporary legal disputes around AI training data, the EU AI Act, and U.S. copyright litigation, the paper argues that ownership is being outpaced by technological reality. Three futures are explored: subscription-based access models, reputation economies built on trust and attention, and open-source commons as global infrastructure. Ultimately, the Global South may transition into this post-ownership world more rapidly than the West, where legal and corporate systems remain anchored to outdated notions of exclusivity.